Emotional intelligence and resilience in secondary school students at a public school in the province of Cutervo (Cajamarca, Peru) - Loyola Sheen, Ricardo (2024)
The purpose of this study was to determine the relationship between emotional intelligence and resilience in adolescent students attending a public school in the Peruvian highlands. The research employed a quantitative, non-experimental, cross-sectional, and correlational design. The sample consisted of 417 students aged 14 to 17, enrolled in the third to fifth grades of secondary education at a public school in the province of Cutervo (Cajamarca, Peru). The Bar-On Emotional Intelligence Inventory and the Wagnild and Young Resilience Scale were administered. The results revealed a strong and statistically significant positive correlation between emotional intelligence and resilience (rs = .528; p < .001). Correlations between the dimensions of emotional intelligence and resilience were also positive and significant, except for the correlation between the intrapersonal dimension and that of confidence and feeling good alone, which did not reach statistical significance.